Partial discharges in twisted-pair magnet wires subject to multilevel PWM pulses - Florkowski, Marek; Blaszczyk, Pawel; Klimczak, Pawel (IEEE transactions on dielectrics and electrical insulation, 2017)
Researchers and designers of insulation systems are facing new challenges due to the ubiquitous presence of power electronics devices in power conversion applications across various voltage levels. The stresses applied to insulation systems by power electronic devices require new approaches for evaluating the intensity and frequency content of working electric field strength and degradation processes. Typically these parameters are assessed through the analysis of partial discharges. Multilevel converters are increasingly being implemented in industrial applications due to the advantages they offer for example in efficiency, harmonic distortion and filtering strategies. This paper presents an analysis of partial discharges in a magnet twisted-pair wires subjected to high voltage pulse-width-modulated pulses obtained from a multilevel converter. A comparison between the number of levels and modulation frequencies on partial discharge inception and intensity are presented. As an assessment criterion, the voltage-time product above partial discharge inception level was compared.